Fabrication and characterization of silver nanorods incorporated calcium silicate scaffold using polymeric sponge replica technique - Pawan Kumar; Brijnandan S. Dehiya; Anil Sindhu; Ravinder Kumar; Catalin I. Pruncu; Anil Yadav (Materials & Design, 2020)
The risk of infection in bones after surgical procedures can be reduced by using antibacterial scaffolds. This study was aimed at preparing a silver nanorods (Ag-nr) incorporated wollastonite (CaSiO3) scaffold using the polymeric sponge replica method. The powdered Ag-nr sample shows an ultrafine microstructure with a minimum rod diameter of 20.8 nm. The Ag nanorods were fabricated by a reflux method and the sol-gel derived Ag-incorporated-CaSiO3 samples (Ag-CaSiO3) were characterized through FTIR, XRD, TEM, SEM, and BET analytical techniques. The electron microscopic results of the scaffold revealed a well-defined porous construction with pore sizes varying from 103 to 164 μm which are suitable for cell infiltration. The Ag-CaSiO3 scaffold showed a brittle behavior with compressive strength of 11.7 MPa. The in-vitro degradation and mineralization behavior of the Ag-CaSiO3 scaffold was investigated using SBF. The Ag-CaSiO3 samples present sound antibacterial effects against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Salmonella typhi without negotiating the formation of apatite layer in simulated body fluid (SBF). The in-vitro cell viability and attachment studies with MG-63 cells using Alamar blue assay confirmed the cytocompatible nature of Ag-CaSiO3. The rationally designed Ag-CaSiO3 sample can generate a healthier substitute for bone tissue engineering compared to other similar materials.